Wayang Hip Hop Dekonstruksi Budaya Tradisi di Yogyakarta - Aji Santoso Nugroho (Institut Seni Indonesia Yogyakarta, 2018)
This paper aims to observe the presence of the Hip Hop Puppet in the middle of the Yogyakarta community which is developing quite dynamically. Talcott Parsons’s theory of social action and Derrida’s deconstruction theory is used as a theoretical framework to explain the presence of this Hip Hop Puppet. The theory was chosen because the Hip Hop Puppet was created by Ki Catur Kuncoro by fusing two cultures and simultaneously deconstructing the pure shadow puppets that were present first. Hip Hop puppets were created to meet the needs of today’s young generation. The Hip Hop Puppet was created by Ki Catur Kuncoro with the aim that the young generation does not lose their cultural roots and at the same time still be able to keep up with the times. In addition, the Hip Hop Puppet is intended as an alternative media to convey criticism and proof that traditional culture can be aligned with modern culture. The acceptance of the Hip Hop Puppet as a spectacle that attracts audiences from all walks of life, proves that there is a cultural change in the middle of the social life of the people of Yogyakarta. Tulisan ini bertujuan mengamati kehadiran Wayang Hip Hop di tengah masyarakat Yogyakarta yang berkembang cukup dinamis. Teori Talcott Parsons tentang tindakan sosial dan teori dekonstruksi Derrida digunakan sebagai kerangka teori untuk menjelaskan kehadiran Wayang Hip Hop ini. Dipilihnya teori tersebut karena Wayang Hip Hop diciptakan oleh Ki Catur Kuncoro dengan meleburkan dua kebudayaan dan sekaligus mendekonstruksi wayang kulit purwa yang telah hadir lebih dulu. Wayang Hip Hop diciptakan untuk memenuhi kebutuhan generasi muda zaman sekarang. Wayang Hip Hop diciptakan Ki Catur Kuncoro dengan tujuan agar generasi muda tidak kehilangan akar kebudayaan dan sekaligus tetap dapat mengikuti arus perkembangan zaman. Selain itu Wayang Hip Hop dimaksudkan sebagai media alternatif untuk menyampaikan kritik dan sebuah pembuktian bahwa budaya tradisi dapat disejajarkan dengan budaya modern. Diterimanya Wayang Hip Hop sebagai tontonan yang menarik penonton dari semua kalangan, membuktikan bahwa terjadi perubahan budaya di tengah kehidupan sosial masyarakat Yogyakarta.